Teachers' and Students' Perceptions of Android-based Mathematics Learning Media Development by Integrating GeoGebra - Ayu Mastura; M Ikhsan; Mailizar Mailizar (Indonesian Journal of Mathematics Education, 2022)
The utilization of technology as a learning resource or media has been widely used as an innovation to promote learning. It is expected to stimulate the thoughts, feelings, interests, and attention of students in learning. The purpose of this study is to find out teachers’ and students’ perceptions of the need for Android-based mathematics learning media on geometry transformation. This research used a descriptive qualitative approach. Data was collected using validated questionnaires for teachers and students. The subjects of this study were mathematics teachers and 2nd-grade students at a senior high school in Aceh, Indonesia. The data was analyzed using descriptive statistical methods. The results showed that the geometry transformation subject was difficult for students. The various formulas and the material's abstractness make understanding the transformation subject challenging. Less attractive learning sources or media and a lack of variety in learning approaches are also influential factors. This study also revealed that teachers were still not optimal in utilizing the various available technological media. Thus, teachers and students need interesting and innovative learning media that can assist students in exploring abstract mathematical concepts, especially geometry transformation. These results became an important reference in the development of Android-based learning media assisted by GeoGebra Software.